2016
DOI: 10.6002/ect.2015.0200
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: Renal allograft function and graft survival depends on many factors, including the source of the graft, immunologic matching between donor and recipient, incidence of acute rejection, and recurrence of the original kidney disease. This work aimed to evaluate the effects of the original kidney disease on patient and graft survival. Materials and Methods: This was a retrospective, single-center study that included 2189 kidney transplant recipients who were transplanted at The Urology and Nephrology C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…This represents 39.44% of all patients in these studies. Only Mashaly et al [17] distinguished between acute and chronic rejections (353 vs 197). Seven (7) episodes of delayed graft function were recorded (Pontin et al [32], Elsayed et al [33]).…”
Section: Complications and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…This represents 39.44% of all patients in these studies. Only Mashaly et al [17] distinguished between acute and chronic rejections (353 vs 197). Seven (7) episodes of delayed graft function were recorded (Pontin et al [32], Elsayed et al [33]).…”
Section: Complications and Managementmentioning
confidence: 99%
“…In the postoperative period, there were 434 cases of acute tubular necrosis across 6 studies [17,18,23,26,36,43], and a total of 2248 post-op infections were recorded in 11 studies [15, 17-19, 23, 25-27, 33, 41, 43], totalling 11.36% of all patients in the studies reviewed. Bacterial infections were seen in 30.56% of all patients, which were the most significant cause of post-op infection of known cause, with viral infections (seen in 13.56% of patients) and tuberculosis (in 4.75% of patients) making up the rest.…”
Section: Complications and Managementmentioning
confidence: 99%
“…It was assumed that 18%-22% of the death-censored kidney allograft losses was attributed to allograft GN ( de novo and recurrent)[ 7 ], the second most common cause of death-censored graft losses[ 18 ] and third most prevalent cause of uncensored graft losses[ 9 , 16 ]. However, Mashaly et al[ 19 ] observed that the best allograft survival of kidney transplantation was noted in recipients whose end stage renal failure was due to polycystic kidney disease followed by those who had urologic disease and then those who had GN as the cause of renal failure. The recurrent GN disease has a wide variety of drawbacks deranging allograft function, which made it occupy the third most common etiology of allograft loss after death with a functioning graft and chronic allograft glomerulopathy, an assumption that was agreed by Fairhead and Knoll[ 20 ] (2010) who declared that the recurrent GN disease is a major determinant of the long term graft survival (Figure 1 ).…”
Section: Graft Survival In Recurrent Gn Disease After Renal Transplanmentioning
confidence: 99%
“…It can recur immediately post-transplantation, or recur lately, where its diagnosis is usually masked by the secondary FSGS resulting from the reduced total nephron mass, or due to other causes, e.g ., iatrogenic[ 20 , 44 ]. Of all causes of the FSGN, “genetic” subtype showed the least incidence of recurrence[ 19 , 45 , 46 ]. On the other hand, podocin mutations did not show a decreased risk of recurrence[ 45 ].…”
Section: Significance Of “Protocol Biopsy” For Early Diagnosis Of Recmentioning
confidence: 99%